Synthesis and chemical exploration of novel pyrano[2,3-c]pyrazole-3-carboxylate and its derivative via one-pot reaction - Maarop, Muhammad Siddiq (2019)
A simple and green approach for the synthesis of fusedpyrano[2,3-clpyrazole-3carboxylate and spiropyrano[2,3-c]pyrazole-3-carboxylate derivatives was developed. The synthesis was achieved under the optimized condition of domino one-pot, fourcomponent reaction of diethyl oxaloacetate, hydrazine hydrate, aldehyde or ketones and malanonitrile in refluxing acidic ethanolic solution under non-catalytic system. As the results, the desired compound was obtained in relatively high yield which is 82% yields. In order to extend the scope of study, the derivatives of hydrazine hydrate, cyano ester and diketo compound were used to obtain a new class of pyrano[2,3c]pyrazole-3-carboxylate derivatives. This procedure displayed high regioselectivity, furnished generally moderate to excellent yields (70-90% yield) and used easily access starting materials, and displayed operational simplicity. This four-component reaction presumably proceeds via sequential reactions of pyrazole synthesis, Micheal addition and Thorpe-Ziegler cyclization reaction. By having pyrano[2,3-c]pyrazole-3carboxylate in hands, a chemical exploration on the aminonitrile side of the compounds was done by specifically focus on the ring extension for multicyclic compounds through C-C and C-S ring extension. At the end of this study, a total of 30 derivatives which some are new were successfully synthesized.